In the Labyrinth of Forgetfulness: Charley Grainger’s Joycean Journey in Christine Dwyer Hickey’s Cold Eye of Heaven - Sikorska , Liliana (Porównania, 2021)
Cold Eye of Heaven (2011) shows pre-Brexit Dublin steeped in the post-Celtic Tiger anxieties. The novel narrates the life of a contemporary Everyman, Charley Grainger, known as Farley, from his final moments back to his childhood. Thus, Farley’s journey envisages both a Joycean interior monologue depicting his old-age bafflement in the meanders of memory and a realistic description of the character’s bewilderment at the changes in the cityscapes of the Dublin of 2010. The present paper is a comparative study of the first two chapters of the novel in reference to the history of the city present in the entire text, through the use of the tropes of the mental and urbane labyrinths. Imbued with the allusions to current reality, i.e., the presence of immigrants, Hickey’s observations are in line with Joycean anti-nationalism, as the story offers a nostalgia-stricken picture of the inevitable economic transformation of the metropolis.